AGE DISCRIMINATION AGAINST JOB APPLICANTS IN INDONESIA FROM A HUMAN RIGHTS PERSPECTIVE - Aryasuta Faharsyah Setiawan (Justisi: Jurnal Ilmu Hukum, 2026)
The majority of job vacancies available in Indonesia include age requirements with very young maximum limits, generally around thirty years old or even as low as twenty-five. This condition results in job seekers over the age of thirty having very limited options in the labor market. In reality, at that age, individuals often have a strong need for employment. This study employs a normative legal research method. The findings indicate that age restriction requirements applied to all types of jobs give rise to various problems. In Indonesia, companies frequently impose unreasonable employment requirements, and to date, there is no clear regulation specifically addressing age discrimination or ageism against workers. The competent authorities should therefore establish written regulations to protect the rights of job seekers, grounded in human rights principles, rather than leaving such matters solely to company discretion.